(3GdeLGdS GdeDjOjIs - (3gHg Gddg Hf ehSi Hf YeQGf GdTjQGRj,J (B470 (3g` s ((3fGUQ MSf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi MbjbI UfYJg fai GdUaGJ s
(3BNQgG (B:s
(3LYdce Gddg ef GdbGFdjf(B: (3hfRYfG eG ai UOhQge ef Zd ENhGfkG Ydi SQQ eJbGHdjf MSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3eLGdS GdeGFI GdKGefIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI s
Keywords: (3GdJhMjO hGdedd hGdfMds